Rancangan Storyboard Aplikasi Pengenalan Isen-Isen Batik Berbasis Multimedia Interaktif - Renna Yanwastika Ariyana; Erma Susanti; Prita Haryani (Yayasan Literasi Sains Indonesia, 2022)
Culture is a wealth that must be maintained and preserved by the people of Indonesia. One of the Indonesian cultures that is still growing and developing today is the art of batik. Batik is a cultural heritage that has been designated by UNESCO since 2009 as a human heritage for oral and non-material culture (Masterpieces of the Oral and Intangible Heritage of Humanity). Batik has its own beauty, a variety of color patterns and curves of lines strung together into a beautiful unit that is written on the cloth. Adding aesthetic value in the form of isen is a very appropriate thing to beautify batik cloth. In every design, patterns and motifs contained in the fabric, of course it has its own meaning and philosophy. The aesthetic value in batik isen is an addition to the soul of batik, this is because isen is only used to add decoration to enrich the motif as well as to build a certain meaning that the creator wants to convey. Designing technology in the form of interactive multimedia applications as outlined in a storyboard is one of the important steps that must be taken in developing applications for introducing batik isen-isen. The results of the research carried out are, a storyboard design that has been completed has been implemented into an interactive multimedia application to introduce isen-isen to the public. The results of tests carried out using a black box test, it was found that the application was running according to the function and design of the storyboard that was made.